How digitalized is work in large German workplaces, and how is digitalized work perceived by workers? A new employer-employee survey instrument - Mareike Reimann; Anja Abendroth; Martin Diewald (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
Digitalization of work has been made responsible for an increase in labor market inequalities, not only with respect to job loss, but also concerning an increased polarization of the remaining jobs due to processes of devaluation and upgrading of jobs and occupations. However, the discussion about possible consequences is quite polarized and not very sophisticated regarding different technologies and different implementations of the same technology. To understand changes due to digitalization processes, we suggest measuring the implementation of digitalized work both at the individual employee and at the workplace level, because decisions about how digital assistance systems are implemented are made by the latter. Existing representative surveys in Germany so far miss to provide such a comprehensive overview of digitalized work in different occupations and workplaces, as well as their implications for workers. The aim of this paper is to present a newly developed multidimensional measurement of digitalized work implemented in a representative linked employer-employee study design. The instrument aims at measuring the prevalence of various dimensions of digitalized work (the use of digital communication, digital information, digital regulation and control, working with robots) and how those are perceived by workers. – – Die Digitalisierung von Arbeit wird für die Zunahme von Arbeitsmarktungleichheiten (mit)verantwortlich gemacht, nicht nur bezüglich Arbeitsplatzverlust, sondern auch bezogen auf die Polarisierung bestehender Jobs durch einen Prozess der Abwertung und Aufwertung von Berufen und Tätigkeiten. Die Diskussion über mögliche Konsequenzen ist jedoch wenig differenziert in Bezug auf verschiedene Technologien oder unterschiedliche Implementationen der gleichen Technologie. Um Veränderungen durch Digitalisierungsprozesse zu verstehen, ist eine Messung digitalisierter Arbeit auf Beschäftigten- wie auch auf Betriebsebene sinnvoll, da Entscheidungen über den Einsatz digitaler Unterstützungssysteme in Betrieben getroffen werden. In repräsentativen Erhebungen in Deutschland fehlt bislang ein solch umfassender Überblick über digitalisierte Arbeit und ihre Konsequenzen in verschiedenen Berufen und Arbeitsplätzen. Ziel des vorliegenden Beitrags ist es, ein neu entwickeltes, multi-dimensionales Instrument zur Messung digitalisierter Arbeit im Rahmen eines Linked Employer-Employee Studiendesigns vorzustellen. Das Instrument zielt auf eine Bestandsaufnahme der Digitalisierung in Arbeitsorganisationen entlang verschiedener Dimensionen digitalisierter Arbeit (die Nutzung digitaler Kommunikation, digitaler Information, digitaler Regulierung und Kontrolle und der Arbeit mit Robotern) und ihrer Wahrnehmung durch Beschäftigte ab.
Keywords: 330; Digitalization; Digitalized work; Employer-employee; Inequality; Polarization